2008
DOI: 10.1186/1471-2458-8-359
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of breast cancer risk factors and practice of breast self examination among high school students in Turkey

Abstract: Background: Young breast cancer patients have a lower rate of survival than old breast cancer patients due to being diagnosed at advanced stages. Breast self-examination makes women more "breast aware", which in turn may lead to an earlier diagnosis of breast cancer. The purpose of this study was to investigate knowledge and practice of breast self-examination and to determine knowledge of risk factors for breast cancer among high school students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
155
8
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(211 citation statements)
references
References 24 publications
43
155
8
5
Order By: Relevance
“…These studies were conducted amongst local female university students. Similar findings were shown in Turkey (Karayurt et al, 2008) and Angola (Sambanje, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…These studies were conducted amongst local female university students. Similar findings were shown in Turkey (Karayurt et al, 2008) and Angola (Sambanje, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…The knowledge of breast cancer symptoms and practice of breast self examination is inadequate among women living in the developing countries (Ahmed et al, 2006;Karayurt et al, 2008;Kumar et al, 2009;Khokher et al, 2012;Radi 2013;Ranasinghe et al, 2013). However there is evidence of significant improvement with the educational and awareness activities (Gupta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of these programs to achieve this objective remains unknown. There are many publications to assess the knowledge level of different groups of women and their attitude towards breast cancer, in the developing countries (Parsa et al, 2005;Parvez and Anwar 2005;Jaffary et al, 2005;Ahmed et al, 2006;Karayurt et al, 2008;Kumar et al, …”
Section: Introductionmentioning
confidence: 99%
“…Karayurt et al (Karayurt et al, 2008) found that media was the primary source of information on BC for 48.6% of participants. Yoo et al (Yoo et al, 2012) found that only 17.2% of subjects obtained BSE information from a physician or nurse.…”
Section: Discussionmentioning
confidence: 99%